Does Equality Spring from Schools? : An Investigation of Assumptions of Equality Among Adolescents of Subaltern Groups - Gardia, Alok; Singh, Ankita (INDIAN EDUCATIONAL REVIEW, 2016)
In the present modern era, all societies across the globe are striving hard to establish and develop a feeling of equality among its citizens. In such efforts education has become a vital tool for formation of a just and equal society. Therefore, it is imperative that the notion of equality should spring from schools. In such premise, the present investigation has been designed to study the experiences of discrimination faced in the schools by adolescents of subaltern sections of the society to answer if equality springs from schools? A survey was conducted among 500 adolescents selected through random sampling technique to study their experiences and assumptions of equality. The findings of the study supports that subaltern students do experience discrimination in schools; different sub-groups experience low to moderate level of discriminations. However, their assumptions of equality were found to be ideal. It was also found that significant negative relation of experiences of discrimination and assumptions of equality exist in the schools. The study advocates minimizing experiences of discrimination by formation of discrimination free school environment so that the dream of establishing equality may spring from school.